Development of Quartet Game Card Media Based on QR Code to Improve Students' Indonesian Understanding at Elementary School - Defi Antika; Sahkholid Nasution (JIP Jurnal Ilmiah PGMI, 2025)
This study was conducted to determine the effectiveness of QR Code-based quartet cards to improve students' understanding of active and passive sentences, and to emphasize the role of teachers in creating an interactive learning atmosphere. The purpose of this article is to examine the feasibility of quartet game media using QR codes to improve students' understanding of active and passive sentences, by considering the aspects of validity, practicality, and effectiveness of quartet media. This type of research adopts a development model or Research and Development (R&D) with the ADDIE approach consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects in this study involved one material expert, one media expert, one language expert, one teacher, and 28 students of class IV-A Private Elementary School (MIS) Hidayatussalam. In this study, two types of data were used, namely qualitative data and quantitative data, the data collection process was carried out with various instruments, such as media and material validation sheets filled in by expert validators, as well as questionnaires about student and teacher responses, and pretest and posttest instrument sheets. The results of the study showed that the validity of media experts gave a score of 98%, material experts gave a score of 86%, while language experts gave a score of 94%. Therefore, the average total validation score reached 94% with the criteria of "very feasible". The practicality obtained from the questionnaire filled out by teachers and students produced a figure of 99% with the category of "very practical". The effectiveness of the media was analyzed through a comparison of pretest and posttest values ​​using the N-Gain test of 0.61% with a range> 0.7 and included in the "moderate" category. From the results of the study, it can be concluded that the quartet card media (KARPET) is feasible to be applied in the Indonesian language learning process on active and passive sentence material in class IV MIS Hidayatussalam.